(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In the contemporary business landscape, characterised by the increasing prevalence of artificial intelligence (AI), organisations of various sizes are striving to understand its role within their operational frameworks. Companies striving to remain competitive in this dynamic environment are compelled to investigate the potential of AI, raising critical questions about the significance, timing, and level of investment required for AI-enabled resources. This paper proposes a debate to include use of AI into the metrics used to assess organizational ambidexterity. A review of pertinent literature on AI and ambidexterity suggests that AI holds considerable importance, and further research on including AI in the measurement scale of both the dimensions of organisational ambidexterity, exploration and exploitation, becomes all the more logical and befitting.